Dermatological problems following spinal cord injury in Korean patients - Han, Zee-A (J Spinal Cord Med, 2015)
OBJECTIVE: To identify dermatological conditions following spinal cord injury (SCI) and analyze these conditions in relation to various characteristics of SCI. DESIGN: Retrospective chart review. SETTING: National Health Insurance Corporation Ilsan Hospital of Korea, Rehabilitation Center, Spinal Cord Unit. PARTICIPANTS: Patients treated for SCI who were referred to dermatology for dermatological problems, 2000–2012. RESULTS: Of the 1408 SCI patients treated at the spinal cord unit, 253 patients with SCI were identified to have been referred to dermatology for skin problems and a total of 335 dermatological conditions were diagnosed. The most common dermatological finding was infectious (n = 123, 36.7%) followed by eczematous lesions (n = 109, 32.5%). Among the infectious lesions, fungal infection (n = 76, 61.8%) was the most common, followed by bacterial (n = 27, 21.9%) lesions. Seborrheic dermatitis (n = 59, 64.1%) was the most frequent eczematous lesion. Ingrown toenail occurred more frequently in tetraplegics whereas vascular skin lesions occurred more commonly in patients with paraplegia (P < 0.05). Xerotic dermatitis showed a higher occurrence within 12 months of injury rather than thereafter (P < 0.05). Of these, 72.4% of the infectious and 94.7% of the fungal skin lesions manifested below the neurological level of injury (NLI; P < 0.001) and 61.5% of the eczematous lesions and 94.9% of seborrheic dermatitis cases occurred above the NLI (P < 0.001). There was no significant difference in dermatological diagnoses between patients with neurologically complete and incomplete SCI. CONCLUSION: The most common dermatological condition in patients with SCI among those referred to dermatology was fungal infection, followed by seborrheic dermatitis. Although dermatological problems after SCI are not critical in SCI outcome, they negatively affect the quality of life. Patients and caregivers should be educated about appropriate skin care and routine dermatological examinations.